Arthroscopic Assisted Percutaneous Screw Fixation of a Postage Stamp Anterior Glenoid Fracture - Yildirim, K; Beyzadeoglu, T (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
Bio-absorbable anchors are widely used for Bankart repair in shoulder instability surgery. Suture anchor placement for labral repair may give rise to osteolysis and/or create stress risers in the glenoid rim, which may be the underlying reasons for glenoid rim fracture with a fracture line passing through previous anchor placement sites, the so-called "postage stamp fracture". Intraarticular fractures of the glenoid have been treated via open reduction and internal fixation through an arthrotomy, which may lead to potential postoperative complications like infection, neurovascular injuries, joint stiffness, and a long recovery period. Thus, arthroscopic techniques for the reduction and fixation of glenoid fractures have been developed. We present a case of anterior glenoid rim postage stamp fracture 9 years after glenohumeral instability surgery in a 29- year-old male. The fracture and recurrent instability were treated via arthroscopic Bankart revision repair and arthroscopic assisted percutaneous screw fixation, where the arthroscopic fracture reduction and definitive fixation were performed separately and before Bankart repair, which is different from the techniques defined in the literature previously. The patient was able to return to work at 6 weeks, to fitness training without pain or restriction at 3 months, and contact sports 6 months postoperatively. Key words: Bankart fractures, bony Bankart lesion, osseous Bankart lesion, shoulder dislocation, arthroscopy.
Keywords: Shoulder Joint; Arthroscopy; nestabilita kloubu; artroskopie; luxace ramenního kloubu; mužské pohlaví; Philately; Shoulder Dislocation; Adult; Bone Screws; ramenní kloub; recidiva; lopatka; Joint Instability; Scapula; Humans; Recurrence; filatelie; kostní šrouby; dospělí; lidé; Male